Pengaruh Penggunaan Media Papan Cerdas Perkalian Terhadap Hasil Belajar Matematika Materi Perkalian Siswa Kelas II di SD Negeri 75 Buton - Rismayani Armin; Waode Hensi Purwati (Jurnal Akademik Pendidikan Matematika, 2021)
The objective of the research was to know the effect of using multiplication smart board media toward students’ achievement on multiplication subject at grade II of SD Negeri 75 Buton, in academic year 2019/2020. This research was a quantitative research using pretest-posttest control group design. Sample was taken using simple random sampling technique, which was gained from population. There were 2 classes used as the sample, namely group II A as control group, which consisted of 8 students, and group II B as an experiment group, which consisted of 8 students. Based on the result of posttest, it found that students’ score from experiment group was higher than students’ score from control group. Classical completeness from experiment group = 77.5, and it was higher than control group = 73.5. based on the result of hypothesis test using t-test, then it found that tcount = 0,187, with df = 14 sig.(2-tailed) where 0.001 < a (0.05). Therefore, it could be concluded that H0 was rejected and H1 was accepted. This result indicated that there was any effect of using multiplication smart board media toward students’ achievement on multiplication subject at grade II of SD Negeri 75 Buton.